The Human Development Index as an Indicator of Economic Development. An Assessment Based on a Comparative Case Study of Five European Post‑Socialist Countries - Gruczyńska, Anna (Annales. Etyka w Życiu Gospodarczym, 2018)
The aim of the paper is to evaluate the Human Development Index (HDI) as an indicator of economic development. The analysis is based on case studies of five post‑socialist countries: the Czech Republic, Estonia, Hungary, Lithuania, and Poland. To carry out the assessment of the HDI, two approaches are employed. The first involves comparing the HDI values to seventeen other indicators related to different aspects of development chosen with reference to Amartya K. Sen’s approach. The second approach refers to public opinion surveys provided by the Eurobarometer and the European Quality of Life Survey programs. In the light of the analysis, it can be said that the HDI is a fairly good measure of economic development. However, certain important dimensions which have a significant impact on people’s living conditions are neglected. Knowing about Sen’s influence on the creation of the HDI and the emphasis he put on the relationship between democracy and development, it may be surprising that such neglected dimensions include the state of democracy.